Assessing the Influence of Planning on Selected Instructional Behaviours of Physical Education Students from University of Education, Winneba on Internship in the Volta Region of Ghana - Nyavor, Lawson Gordon; Sorkpor, Richmond Stephen; Fiadzo, Simon (International Journal of Scientific Research and Management (IJSRM), 2018)
The purpose of this study was to assess the influence planning have on selected instructional behaviours of a group of student-interns across two teaching conditions, one planned and one unplanned. Eight physical education student-interns from the Department of health, Physical education, Recreation and Sports of University of Education, Winneba taught two 30-minute lessons to Senior High School and College of Education students. Lesson plans were developed for the first lesson (planned condition) but not the second (unplanned condition). All lessons were videotaped and employed in the data analyses. Three data collection instruments were used for the analysis of selected teaching behaviours: (a) an event recording instrument for coding teacher verbal feedback statements, (b) the Qualitative Dimensions of Lesson Introduction, Task Presentation, and Lesson Closure (QDITC) system and an interview. The results suggest that planning has a positive influence on student-interns’ instructional behaviours. For teachers in training, it seems that planning is important to the employment of "effective" teaching behaviours in the interactive teaching environment.